TRÁFICO DE ENTORPECENTES - Nascimento, Amanda Nárgela Bueno; Souza, Agmar Gomes de; Belo, Bianca Aparecida; Silva, Daiana Oliveira da; Katayama, Juliana Tiemii; Oliveira, Mariana Leticia S.; Silva, Flavia Alessandra Naves da; Macena, Lincoln Villas Boas (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
... ver texto na íntegra.